Pengaruh Asertivitas Siswa dan Persepsi pada Matematika Terhadap Prestasi Belajar Matematika Siswa Kelas IX SMP Shalahuddin Malang - Heru Sofian (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2020)
This study aims to determine: (1) the effect of student assertiveness and perception on mathematics on student mathematics learning achievement. (2) the effect of student effectiveness on students' mathematics learning achievement. (3) the effect of perception on mathematics learning achievement. The results of this study concluded, (1) students' assertiveness had a positive and significant effect on mathematics learning achievement of students of class IX of SMP Shalahuddin Malang, (2) Perception on mathematics had a positive and significant effect on mathematics learning achievement of students of class IX of SMP Shalahuddin Malang (3) Both asertivity students and students' perceptions of mathematics simultaneously influence the student's mathematics learning achievement. That is, the higher the student's assertiveness and the better the students' perceptions of mathematics the more mathematics learning achievement of students of class IX of SMP Shalahuddin Malang.